Recent changes in trends of opioid overdose deaths in North America - Sameer Imtiaz; Kevin D. Shield; Benedikt Fischer; Tara Elton-Marshall; Bundit Sornpaisarn; Charlotte Probst; Jürgen Rehm (BMC, 2020)
Abstract Background As several regulatory and environmental changes have occurred in North America, trends in overdose deaths were examined in the United States (US), Ontario and British Columbia (BC), including changes in consumption levels of prescription opioids (PO) and overdose deaths, changes in correlations between consumption levels of PO and overdose deaths and modeled differences between observed and predicted overdose deaths if no changes had occurred. Methods Consumption levels of PO included defined daily doses for statistical purposes per million inhabitants per day for the US and Canada (2001-2015). Overdose deaths included opioid overdose deaths for the US (2001-2017) and Ontario (2003-2017) and illicit drug overdose deaths for BC (2001-2017). The analytic techniques included structural break point analyses, Pearson product-moment correlations and multivariate Gaussian state space modeling. Results Consumption levels of PO changed in the US in 2010 and in Canada in 2012. Overdose deaths changed in the US in 2014 and in Ontario and BC in 2015. Prior to the observed changes in consumption levels of PO, there were positive correlations between consumption levels of PO and overdose deaths in the US (r = 0.99, p < 0.001) and Ontario (r = 0.92, p = 0.003). After the observed changes in consumption levels of PO, there was a negative correlation between consumption levels of PO and overdose deaths in the US (r = − 0.99, p = 0.002). Observed overdose deaths exceeded predicted overdose deaths by 5.7 (95% Confidence Interval [CI]: 4.8-6.6), 3.5 (95% CI: 3.2-3.8) and 21.8 (95% CI: 18.6-24.9) deaths per 100,000 people in the US, Ontario and BC, respectively in 2017. These excess deaths corresponded to 37.7% (95% CI: 31.9-43.6), 39.2% (95% CI: 36.3-42.1) and 72.2% (95% CI: 61.8-82.6) of observed overdose deaths in the US, Ontario and BC, respectively in 2017. Conclusions The opioid crisis has evolved in North America, as a sizeable proportion of overdose deaths are now attributable to the several regulatory and environmental changes. These findings necessitate substance use policies to be conceptualized more broadly as well as the continued expansion of harm reduction services and types of pharmacotherapy interventions.